2020
DOI: 10.1155/2020/9876363
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Zinc Sulfate in Improving Fertility in Obese Rats Analyzed by Sperm Proteomic Analysis

Abstract: This study investigates the mechanism underlying the improving effect of zinc on fertility in obese rats using proteomics. The effects of three different doses of ZnSO4 on spermatogenesis and hormone levels were studied. Testicular spermatogenesis was observed by HE staining. Serum estrogen and testosterone levels were measured by chemiluminescent microparticle immunoassay. Sperm proteomic analysis was performed by liquid chromatography-mass spectrometry. The DAVID database was used to perform the GO enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…However, its combination with ginger powder had a more significant effect than zinc alone. Our results were consistent with the results of previous studies (Ma et al, 2020; Schisterman et al, 2020) showing zinc supplementation greatly improves reproductive performance in people suffering from infertility. Our results showed that co‐administration of zinc with lead could improve tissue damage, sperm parameters and spermatogenesis process, and the pituitary‐gonadal axis activity.…”
Section: Discussionsupporting
confidence: 93%
“…However, its combination with ginger powder had a more significant effect than zinc alone. Our results were consistent with the results of previous studies (Ma et al, 2020; Schisterman et al, 2020) showing zinc supplementation greatly improves reproductive performance in people suffering from infertility. Our results showed that co‐administration of zinc with lead could improve tissue damage, sperm parameters and spermatogenesis process, and the pituitary‐gonadal axis activity.…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted on LC showed a significant increase in plasma testosterone level in male adult albino mice that were treated with cadmium chloride at dose 0.35 mg/kg [ 38 ]. Similarly, a study conducted on ZnSO 4 in improving fertility also supported that Zn had a positive effect on testosterone level and semen quality in infertile 7-week-old Sprague Dawley rats [ 39 ]. CoQ10 also reversed the testicular damage associated with cadmium toxicity by enhancing the levels of LH and testosterone in rodents likewise the present study [ 39 ].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, a study conducted on ZnSO 4 in improving fertility also supported that Zn had a positive effect on testosterone level and semen quality in infertile 7-week-old Sprague Dawley rats [ 39 ]. CoQ10 also reversed the testicular damage associated with cadmium toxicity by enhancing the levels of LH and testosterone in rodents likewise the present study [ 39 ].…”
Section: Discussionmentioning
confidence: 90%
“…Research has shown that Zn supplementation enhances the physical characteristics of semen, including ejaculate volume, sperm count, motility, seminal plasma antioxidants, and fertility rate (Amen and Muhammad 2016;Rahman et al 2014;El-Speiy and El-Hanoun 2013;Rafique et al 2010;Ghasemi et al 2009;Oliveira et al 2004;Maldjian et al 1998). Rats treated with Zn showed an increase in sperm count, sperm motility, and testosterone levels, as well as improved testicular structure and spermatogenesis abnormalities caused by obesity (Ma et al 2020). However, other studies have suggested no significant association between Zn and sperm quality (Eggert-Kruse et al 2002;Lin et al 2000).…”
Section: Discussionmentioning
confidence: 95%